Evaluating the Environmental Impact of Heat Pump Systems: An Integrated Approach to Sustainable Building Operations - Mahdiyeh Zafaranchi; William T. Riddell; Nicholas B. Chan; Elizabeth Saliba; Luke Leung (Energies)
This study evaluates the energy consumption and embodied carbon emissions of various heat pump systems for an office building in Chicago, IL, U.S., over a 50-year lifespan, including the operation, manufacturing, and construction phases. The analyzed systems include air source heat pumps (ASHP) in Air to Air and Air to Water configurations, and ground source heat pumps (GSHP) in Soil to Air and Soil to Water configurations. A traditional HVAC system serves as the baseline for comparison. Advanced simulation tools, including Rhino, Grasshopper, TRACE 700, and One Click LCA, were used to identify the optimal HVAC system for sustainable building operations. Unlike prior studies focusing on GSHP versus traditional HVAC systems, this research directly compares GSHP and ASHP configurations, addressing a significant gap in the sustainable HVAC system design literature. The GSHP (Soil to Water) system demonstrated the lowest energy intensity at 100.8 kWh/m2·yr, a 41.8% improvement over the baseline, and the lowest total embodied carbon emissions at 3,882,164 kg CO2e. In contrast, the ASHP (Air to Air) system, while reducing energy consumption relative to the baseline, exhibited the highest embodied carbon emissions among the heat pump configurations due to its higher operational energy demands. The study highlights the significance of the operating phase in embodied carbon contributions. These findings emphasize the importance of a holistic design approach that considers both operational and embodied impacts to achieve sustainable building designs.